Analisis Terhadap Metode Kuliah Daring dan Biaya Tranposrtasi Mahasiswa Indonesia Dalam Masa Pandemi COVID-19: Analysis on the Method of Online Learning and Transportation Budgets from Indonesian Students During the Pandemic COVID-19 - Esther Sanda Manapa; Eliyah Acantha M Sampetoding; Monica Natalin; Benardo Sinambela; Dwi Ivana L Sitohang; Yusri Anugerah M Ambabunga; Valian Yoga P Ardhana (Journal Dynamic Saint, 2020)
This study aims to analyze the effect of the Covid-19 pandemic on the applications and student expenditure during the pandemic. The Covid-19 pandemic caused the government through the Ministry of Education and Culture to announce teaching and learning activities carried out from home using the online method. There are several complaints with the use of online methods, one of which is opinion about the increase in fees for the purchase of data package pulses. The opinion said that student spending increased due to the purchase of data package pulses. This study tries to conduct a survey and analysis specifically comparing student costs before and after co-19. During a pandemic, students spend more credit than before the pandemic which is 10.8% on topping up. But it was revealed that spending on pandemic students was less than before the pandemic with the smallest percentage of 46.9%. While applications that are often used in online lecture methods are Google Classroom with 74.7%, Zoom 67%, and WAG 35.3%. It is hoped that this initial research can support and provide input to policy makers in education institutions during lectures during the pandemic.